ds= i dydz + j dzdx + k dxdy
z=g(x,y)
F= iF1 + j F2 + k F3
F.ds= F1. dy dz + F2 . dzdx + F3 dxdy
For integrating above F3 dxdy is Ok
But to integrate about say F2dzdx
How to find dz ?
Some one told it is - dz/dy.dy partial derivative and negative also.
How it came so?
So F2dzdx becomes F2(x,y,z(x,y)) . [-dz/dx](x,y) . dxdy
z=g(x,y)
F= iF1 + j F2 + k F3
F.ds= F1. dy dz + F2 . dzdx + F3 dxdy
For integrating above F3 dxdy is Ok
But to integrate about say F2dzdx
How to find dz ?
Some one told it is - dz/dy.dy partial derivative and negative also.
How it came so?
So F2dzdx becomes F2(x,y,z(x,y)) . [-dz/dx](x,y) . dxdy